2020
DOI: 10.1039/c9ra07009e
|View full text |Cite
|
Sign up to set email alerts
|

Benzyl salicylate from the stems and stem barks of Cornus walteri as a nephroprotective agent against cisplatin-induced apoptotic cell death in LLC-PK1 cells

Abstract: Benzyl salicylate from Cornus walteri can be a nephroprotective agent against cisplatin-induced oxidative stress and apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Our results on detecting PARP-1 cleavage after treatment with 50 µM CisPt for 24 h are similar to the study of Ju et al 62 who detected the PARP-1 cleavage in HK-2 cells treated with 40 µM CisPt for 24 h. JNKs were reported to be strongly activated via phosphorylation in cells incubated with cisplatin 63 . In our study, expression of phosphorylated JNK isoforms (JNK1 and JNK2) was elevated after cisplatin treatment in all time intervals in dose-dependent manner compared to control cells which is similar to reported finding on increased pJNK expression in HeLa cells after incubation with 50 and 100 µM CisPt for 6 h 64 , and in pig kidney epithelial cells after 25 µM CisPt treatment for 24 h 65 .…”
Section: Discussionsupporting
confidence: 91%
“…Our results on detecting PARP-1 cleavage after treatment with 50 µM CisPt for 24 h are similar to the study of Ju et al 62 who detected the PARP-1 cleavage in HK-2 cells treated with 40 µM CisPt for 24 h. JNKs were reported to be strongly activated via phosphorylation in cells incubated with cisplatin 63 . In our study, expression of phosphorylated JNK isoforms (JNK1 and JNK2) was elevated after cisplatin treatment in all time intervals in dose-dependent manner compared to control cells which is similar to reported finding on increased pJNK expression in HeLa cells after incubation with 50 and 100 µM CisPt for 6 h 64 , and in pig kidney epithelial cells after 25 µM CisPt treatment for 24 h 65 .…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, benzyl salicylate ( 15 ) was more efficient than L-NMMA in inhibiting NO production in LPS-activated RAW 264.7 macrophages. In previous studies, benzyl salicylate was shown to be an active compound with estrogenic activity [ 44 ], and a protective agent against cisplatin-induced damage to cells of the LLC-PK1 kidney proximal tubule cell line [ 21 ]. However, to the best of our knowledge, there are no reports available regarding the inhibition of NO production in LPS-activated RAW 264.7 macrophages by benzyl salicylate.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we identified new tirucallane triterpenoids (cornusalterins N-P) in C. walteri , along with bioactive tirucallane triterpenoids that control adipocyte and osteoblast differentiation [ 20 ]. A nephroprotective agent has also been identified in C. walteri extracts using a model of cisplatin-induced cell death in LLC-PK1 kidney proximal tubule cell line; it was found to decrease the proteins involved in intrinsic apoptosis pathway [ 21 ]. As C. walteri extract has been known to inhibit NO production in RAW 264.7 macrophages stimulated with lipopolysaccharide (LPS) [ 22 ], the present study was carried out for further investigation of the methanol extracts of the stem and stem bark of C. walteri to identify potential anti-inflammatory constituents.…”
Section: Introductionmentioning
confidence: 99%
“…Plants 2021, 10, 431 2 of 8 acid on A2780 human ovarian cancer cells and the renoprotective effect of benzyl salicylate on cisplatin-induced damage in LLC-PK1 kidney proximal tubule cells have been explored and evaluated in our previous studies [16,17]. In the present study, we focused on (-)-leucophyllone, a tirucallane triterpenoid isolated from the further phytochemical investigation of the MeOH extract from C. walteri.…”
Section: Isolation and Identification Of (-)-Leucophyllone From C Wamentioning
confidence: 99%
“…Our previous phytochemical analysis on C. walteri led to the isolation of triterpenoids, including betulinic acid methyl ester, lupenone, lupeol, betulinic acid, methyl 3-O-acetyl betulinate, and sterols such as 6β-hydroxysitostenone, 5α-stigmast-3,6-dione, sitostenone, 3β-sitostanol, and 6α-hydroxy-β-sitostenone [16,17]. Among them, the anticancer effect of betulinic acid on A2780 human ovarian cancer cells and the renoprotective effect of benzyl Plants 2021, 10, 431 2 of 7 salicylate on cisplatin-induced damage in LLC-PK1 kidney proximal tubule cells have been explored and evaluated in our previous studies [16,17]. In the present study, we focused on (-)-leucophyllone, a tirucallane triterpenoid isolated from the further phytochemical investigation of the MeOH extract from C. walteri.…”
Section: Introductionmentioning
confidence: 99%